Enhanced Far-Field Directional Luminescence Emission by a Hybrid Structure Consisting of Silver Channel and Microlens - Zhi-Hui Chen; Hongsheng Quan; Yang Wang; Yibiao Yang (IEEE Photonics Journal, 2019)
In microfluidic detection, the distance between the fluorescent nanoparticles (FNPs) and the structure is usually in far-field range. In previous work, the enhancement of emission will decay exponentially with the increase of the distance between FNPs and the structures, which brings a challenge to the development of high-sensitivity biosensors. In this paper, a hybrid structure consisting of a silver channel and a microlens is proposed to enhance far-field directional emission when the FNP is in far-field range. It is shown that the far-field total power enhancement of our structure is obvious compared to the polymethyl methacrylate channel. This is due to scattering, constructive interference, and resonance modes created by the silver channel and microlens. This structure will contribute to high-sensitivity biosensors.